Fast multiplane functional imaging combining acousto-optic switching and remote focusing - Chong, E; Barreiros, I; Li, B; Kohl, M; Booth, M (Society of Photo-Optical Instrumentation Engineers, 2017)
Networks of neurons are inherently three-dimensional in nature, whereas conventional imaging methods, such as laser scanning two-photon microscopy, usually provide only fast two-dimensional imaging. Rapid volumetric imaging would however be preferable for imaging neurons. To get a more complete picture of the dynamics of the neuron-to-neuron interactions, we have developed a pseudo-parallelised multi-plane two-photon excitation imaging system through the incorporation of an acousto-optic switching and a remote focusing technique into a resonant scanning microscope. This permits the recording of millisecond scale fluorescence transients of calcium indicators from large populations of neurons upon neural firing events at multiple chosen axial planes in very short time frame. While the remote focusing system offers aberration-free axial scanning over a few hundreds of micrometres of depth, the acousto-optic deflector provides high speed optical switching between different laser beam paths in sub-microsecond timescale which in turn, controls the axial focal plane to be targeted. Here, we report on the development of the high temporal resolution multi-plane targeted microscope and its potential application.